Distinction of non-specific low back pain patients with proprioceptive disorders from healthy individuals by linear discriminant analysis - Shokouhyan, Seyed Mohammadreza; Davoudi, Mehrdad; Hoviattalab, Maryam; Abedi, Mohsen; Bervis, Soha; Parnianpour, Mohamad; Brumagne, Simon; Khalaf, Kinda (Frontiers in Bioengineering and Biotechnology, 2022)
The CNS dynamically employs a sophisticated weighting strategy of sensory input, including vision, vestibular and proprioception signals, towards attaining optimal postural control during different conditions. NSLBP patients frequently demonstrate postural control deficiencies which are generally attributed to challenges in proprioceptive reweighting, where they often rely on an ankle strategy regardless of postural conditions. Such impairment could lead to potential loss of balance, increased risk of falling, and LBP recurrence. In this study, linear and nonlinear indicators were extracted from COP and trunk sagittal angle data based on 4 conditions of vibration positioning (vibration on the back, ankle, none or both), 2 surface conditions (foam or rigid), and 2 different groups (healthy and NSLBP patients). Linear discriminant analysis (LDA) was performed on linear and nonlinear indicators to identify the best sensory condition towards accurate distinction of NSLBP patients from healthy controls. Two indicators: Phase Plane Portrait ML and Entropy ML with foam surface condition and both ankle and back vibration on, were able to completely differentiate the NSLBP groups. The proposed methodology can help clinicians quantitatively assess the sensory status of NSLBP patients at the initial phase of diagnosis and throughout treatment. Although the results demonstrated the potential effectiveness of our approach in LBP patient distinction, a larger and more diverse population is required for comprehensive validation.